2016
DOI: 10.1152/ajpheart.00085.2016
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial reverse remodeling after pressure unloading is associated with maintained cardiac mechanoenergetics in a rat model of left ventricular hypertrophy

Abstract: Pressure unloading represents the only effective therapy in increased afterload-induced left ventricular hypertrophy (LVH) as it leads to myocardial reverse remodeling (reduction of increased left ventricular mass, attenuated myocardial fibrosis) and preserved cardiac function. However, the effect of myocardial reverse remodeling on cardiac mechanoenergetics has not been elucidated. Therefore, we aimed to provide a detailed hemodynamic characterization in a rat model of LVH undergoing pressure unloading. Press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
(64 reference statements)
4
12
0
1
Order By: Relevance
“…Moreover, recent evidence also showed that mechano‐energetics recovery contributes to myocardial reverse remodeling with reductions in load (Ruppert et al. ). Although myocardial adaptations to left ventricular assist devices (LVAD) support indicate substantial potential for structural, functional, and molecular plasticity within severely diseased hearts, sustained myocardial recovery after LVAD removal has been reported in only a small percent of cases, although higher rates may be possible (Hellawell and Margulies ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent evidence also showed that mechano‐energetics recovery contributes to myocardial reverse remodeling with reductions in load (Ruppert et al. ). Although myocardial adaptations to left ventricular assist devices (LVAD) support indicate substantial potential for structural, functional, and molecular plasticity within severely diseased hearts, sustained myocardial recovery after LVAD removal has been reported in only a small percent of cases, although higher rates may be possible (Hellawell and Margulies ).…”
Section: Discussionmentioning
confidence: 99%
“…Partial occlusion of the ascending aorta is a common experimental method to induce PO, cardiac hypertrophy, and HF. Although previous studies have shown thickening of the aortic wall, adventitial hyperplasia, collagen deposition, and inflammatory changes, the molecular signaling pathways responsible for this remodeling have not been identified [ 18 , 19 , 20 , 21 , 22 , 23 ]. Importantly, Gal-3 overexpression increased the collagen type I protein levels in VSMCs, and Gal-3 blockade reduces aortic fibrosis and inflammation in other pathological conditions showing its key role in vascular damage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…anaesthesia as previously described1650. After recovering from anaesthesia and on the first and second postoperative day, all animals received meloxicam (1.5 mg/kg p.o.)…”
Section: Methodsmentioning
confidence: 99%